Integration of quality tool and environmental requirements in evaluating a green design concept - Mat Saman, M. Z. (2007)
Green architecture, or green design, is an approach to building that minimizes harmful effects on human health and the environment. The "green" architect or designer attempts to safeguard air, water, and earth by choosing eco-friendly building materials and construction practices.